Adapting classic stories and songs for a school play in english in order for students to develop critical thinking to express possible solutions to current world problems - Murgueytio Gallegos, María Daniela (Pontificia Universidad Católica del Ecuador, 2015)
Students in fourth grade should develop their critical thinking while performing their play at the same time as their second language is reinforced; developing. On the other hand, the writer looks forward to getting this idea applied in the other grades, in order to develop their critical thinking as well. After having observed how kids perform successful school plays year after year, it was high time to deeply analyze how much these plays help to develop students’ ability to think clearly in such a way they understand logical connections of ideas, find solutions to problems, and mainly reflect about their own and others’ ideas, values, beliefs and opinions. Generally, performing a play for kids consists of memorizing lines, rehearsing stage positions and movements again and again, smiling and being as adorable as possible on stage, but it is very untypical to create plays which have a message to be transmitted or that demands students to develop their ability to reason. Developing these two aspects would greatly and potentially benefit the play participants and the audience itself in a way that they can contribute to change many factors that are affecting our society such as environmental problems. On the other hand, this development of students’ critical thinking will eventually make of our present generation the ones that will definitely make a positive change for our world in the present for a better future